Volume 5: 25th International Conference on Design Theory and Methodology; ASME 2013 Power Transmission and Gearing Conference 2013
DOI: 10.1115/detc2013-12588
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder and Constraint-Driven Innovation of a Novel, Lever-Propelled, All-Terrain Wheelchair

Abstract: The Leveraged Freedom Chair (LFC) is a low-cost, allterrain, lever-propelled wheelchair designed primarily for use in developing countries. LFC technology was conceived because 70 percent of wheelchair users in these markets live in rural areas and no currently available mobility aid enables them to travel long distances on rough terrain and maneuver in tight, indoor confines. Because developing world markets impose constraints on cost, durability, and performance, a novel solution was required to satisfy stak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Another product with several types of constraints was a low-cost, all-terrain, level propelled wheelchair proposed by Winter 18 . This was not only a resource constrained object, but also a functionally constrained object: the chair had to be adapted to rough terrain and to tight spaces, to be repairable anywhere and to provide the user with comfortable mobility during the whole day.…”
Section: Empirical Case Studies: How the Design Model Enables Increasmentioning
confidence: 99%
“…Another product with several types of constraints was a low-cost, all-terrain, level propelled wheelchair proposed by Winter 18 . This was not only a resource constrained object, but also a functionally constrained object: the chair had to be adapted to rough terrain and to tight spaces, to be repairable anywhere and to provide the user with comfortable mobility during the whole day.…”
Section: Empirical Case Studies: How the Design Model Enables Increasmentioning
confidence: 99%
“…Only recently have HCD methods been integrated with earlier work in design for development and social innovations [24]. For example, Winters provides an excellent example of work that combines appropriate technology development with design thinking approaches to wheelchair design in the developing world [25,26]. Wood and Mattson [27,28] summarize codesign and user research methods they have found effective on a range of projects in India and Peru.…”
Section: Human-centered Design For Developmentmentioning
confidence: 99%
“…Only recently have HCD methods been integrated with earlier work in design for development and social innovations [10]. Winters provides an excellent example of work that combines appropriate technology development with design thinking approaches to wheelchair design in the developing world [11,12].…”
Section: Design For Developmentmentioning
confidence: 99%